2020
DOI: 10.1080/14616734.2020.1753085
|View full text |Cite
|
Sign up to set email alerts
|

Effect of video-feedback intervention on Turkish mothers’ sensitivity and physical intrusiveness: a randomized control trial

Abstract: We examined the effectiveness of the video-feedback Intervention to Promote Positive Parenting-Sensitive Discipline (VIPP-SD) in enhancing maternal sensitivity and decreasing maternal physical intrusive behaviors among Turkish mothers. Mothers (N = 68; M age = 29.29, SD = 5.20) with their children (M age = 20.04 months, SD = 6.62) participated in a randomized controlled trial with pre-, post-, and follow-up assessments (N intervention = 40, N control = 28). Maternal sensitivity was assessed using the Ainsworth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
(83 reference statements)
0
6
0
Order By: Relevance
“…An important, yet complex open question is, whether parental alexithymic traits can be recognized in early stages of parenthood and furthermore enhance the emotional abilities through interventions. Interventions targeted in enhancing parental abilities, by e.g., increasing the sensitivity (Olds et al, 2002 ; Thomas and Zimmer-Gembeck, 2011 ; Alsancak-Akbulut et al, 2020 ) and diminishing the hostility (Naber et al, 2010 ) in parental caregiving behavior, have been successfully developed, but to our knowledge, not specifically tested or implemented within mothers having pronounced alexithymic traits.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An important, yet complex open question is, whether parental alexithymic traits can be recognized in early stages of parenthood and furthermore enhance the emotional abilities through interventions. Interventions targeted in enhancing parental abilities, by e.g., increasing the sensitivity (Olds et al, 2002 ; Thomas and Zimmer-Gembeck, 2011 ; Alsancak-Akbulut et al, 2020 ) and diminishing the hostility (Naber et al, 2010 ) in parental caregiving behavior, have been successfully developed, but to our knowledge, not specifically tested or implemented within mothers having pronounced alexithymic traits.…”
Section: Discussionmentioning
confidence: 99%
“…Interventions in enhancing parenting behavior in general population have been developed as well. Alsancak-Akbulut et al ( 2020 ) reported promising results on an intervention aiming to enhance maternal sensitivity among a general population sample. In their study, mothers with low educational level participating in a video-feedback intervention designed to enhance sensitive reactions of mothers toward their children showed an increase in sensitivity in comparison to controls (Alsancak-Akbulut et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our surprise, HomVEE considers only studies conducted in high-income countries. Of course, we were excited about the positive HomVEE evaluation of our VIPP-SD suite of parenting intervention programmes, even without excellent VIPP-SD studies in Turkey (Alsancak-Akbulut et al, 2021) and Colombia (Barone et al, 2021). Nevertheless, we argue elsewhere that their criteria for effects including quasi-experimental designs, but conducted in wealthy countries only, and documenting statistical significance instead of effect sizes are not satisfactory from a scientific perspective as presented in this book (see Chapter 8).…”
Section: Meta-analysis Of 25 Vipp-sd Randomised Controlled Trialsmentioning
confidence: 95%
“…It is rooted in a lack of respect for young children's burgeoning autonomy (Ainsworth et al, 1978(Ainsworth et al, /2015, which is known to be a basic childhood need (Deci & Ryan, 2012). Historically, it has been described as problematic parenting requiring targeted interventions in early childhood (Alsancak-Akbulut et al, 2021;Isabella & Belsky, 1991). Numerous studies have suggested that parental intrusiveness leads to children's suboptimal cognitive and socio-emotional development (Pinquart, 2017a(Pinquart, , 2017bPinquart & Kauser, 2018); however, recent studies suggest that intrusive parenting may serve as an appropriate parenting behavior based on differential abilities and cultural contexts (Broomell et al, 2020;Diemer et al, 2021).…”
mentioning
confidence: 99%